Advances in the treatment of relapsing–remitting multiple sclerosis – critical appraisal of fingolimod - Gasperini C; Ruggieri S; Mancinelli CR; Pozzilli C (Dove Medical Press, 2013)
Claudio Gasperini,1 Serena Ruggieri,2 Chiara Rosa Mancinelli,2 Carlo Pozzilli2 1Department of Neurosciences, S Camillo Forlanini Hospital, Rome, Italy; 2Department of Neurology and Psychiatry, Sapienza – University of Rome, Rome, Italy Abstract: Multiple sclerosis (MS) is a chronic inflammatory disorder of the central nervous system, traditionally considered to be an autoimmune, demyelinating disease. Based on this understanding, initial therapeutic strategies were directed at immune modulation and inflammation control. At present, there are five licensed first-line disease-modifying drugs for MS in Europe, and two second-line treatments. Currently available MS therapies have shown significant efficacy throughout many trials, but they produce different side effects. Despite disease-modifying drugs being well known and safe, they require regular and frequent parenteral administration and are associated with limited long-term treatment adherence. Therefore, the development of new therapeutic strategies is warranted. Several oral compounds are in late stages of development for treating MS. Fingolimod is an oral sphingosine-1-phosphate receptor modulator that has demonstrated superior efficacy compared with placebo and interferon β-1a in phase III studies. It has already been approved in the treatment of MS. This review focuses on advances in current and novel oral treatment approaches in MS. We summarily review the oral compounds in this study, focusing on the recent development, approval, and the clinical experience with fingolimod. Keywords: multiple sclerosis, oral compounds, fingolimod, sphingosine-1-phosphate, patient satisfaction, adherence